Epithelial-derived cytokines in the pathogenesis of severe asthma - Pham, Duong Duc; Kim, Tae-Bum (Frontiers in Allergy, 2025)
IntroductionAirway epithelial cells function as the first physical barrier against pathogens and are key regulators of immune responses by producing a wide array of cytokines involved in both innate and adaptive immunity.MethodsThis review summarizes recent advances in our understanding of epithelial-derived cytokines in severe asthma (SA) pathogenesis and highlights promising therapeutic strategies.ResultsEpithelial-derived cytokines can be functionally classified into the following four main groups: alarmins [interleukin [IL]-25, IL-33, thymic stromal lymphopoietin [TSLP]], proinflammatory cytokines (IL-1, IL-6, tumor necrosis factor-α), chemokines (CCL2, CCL5), and antiviral cytokines [interferon (IFN)-α, IFN-β, IFN-λ]. Alarmins are rapidly released in response to epithelial injury and play a pivotal role in initiating immune responses by activating dendritic cells, type 2 innate lymphoid cells, and eosinophils. Proinflammatory cytokines intensify inflammation by promoting immune cell activation and cytokine cascades, while chemokines guide immune cells to sites of injury. Antiviral cytokines enhance epithelial defenses by inducing the expression of antiviral genes. In SA, epithelial-derived cytokines play a central role in initiating and sustaining type 2 (T2) inflammation by activating the IL-4, IL-5, and IL-13 axis, leading to increased eosinophils, elevated serum IgE, and heightened airway hyperresponsiveness. These cytokines are also implicated in non-T2 inflammation, particularly in refractory asthma phenotypes.DiscussionGrowing insights into epithelial cytokines and their complex signaling networks with the airway microenvironment have opened new avenues for developing targeted and personalized treatment in SA.